Sosialisasi Penanganan Demam Pada Anak Dengan Kompres Metode Tepid Water Sponge - Miniharianti; Hijriana, Isni; Wahidanur; Yusnita; Urmila; Nadila, Riska (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2023)
Children under five years of age (toddlers) are a group that is vulnerable to health problems. During the process of growth and development, children often experience illness, especially illnesses caused by infections which are almost always accompanied by fever. Fever is a natural process as the body's defense mechanism against pathogens, but a fever that is too high in children certainly requires appropriate treatment and care because, if the action taken is inappropriate and slow, it can endanger the child's safety and cause other complications such as seizures and decline. awareness. The aim after this health education is to increase parents' knowledge and skills in treating fever using the tepid water sponge method. The method used in this community service activity is active and participatory learning through several stages, namely the preparation stage, implementation stage and evaluation stage with a total of 15 parents participating. The results obtained increased parental knowledge in treating fever using the tepid water sponge method. To health workers, there is a need to provide outreach to parents about treating children with fever using tepid sponge compresses to parents both in the community and hospital settings.